2021
DOI: 10.1002/jmv.27378
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 rapid antigen test in comparison to RT‐PCR targeting different genes: A real‐life evaluation among unselected patients in a regional hospital of Italy

Abstract: We assessed the performance of the Panbio rapid antigen detection (RAD) test for the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and we compared it with the routine reverse transcriptase-polymerase chain reaction (RT-PCR)-based molecular test in a population of 4167 unselected patients admitted to IRCCS Sacro Cuore Don Calabria Hospital. Analysis stratified by cycling threshold (C t ) value of SARS-CoV-2 gene targets indicated that antigen (Ag)-positive C t values were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…Studies carried out in hospital settings, have reported higher sensitivity for the RAT than reported by us [ 21 , 22 ]. For instance, a study carried out in hospital setting in Italy has shown higher PPV and NPV values for RAT than reported by us, with higher sensitivity rates [ 21 ].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Studies carried out in hospital settings, have reported higher sensitivity for the RAT than reported by us [ 21 , 22 ]. For instance, a study carried out in hospital setting in Italy has shown higher PPV and NPV values for RAT than reported by us, with higher sensitivity rates [ 21 ].…”
Section: Discussionmentioning
confidence: 49%
“…Studies carried out in hospital settings, have reported higher sensitivity for the RAT than reported by us [ 21 , 22 ]. For instance, a study carried out in hospital setting in Italy has shown higher PPV and NPV values for RAT than reported by us, with higher sensitivity rates [ 21 ]. Another study in a Swiss University hospital also reported a sensitivity of 65.3% for the SD-Biosensor RAT, which was higher than the 36.5% sensitivity reported by us [ 22 ].…”
Section: Discussionmentioning
confidence: 49%
“…In larger study populations, Panbio sensitivity was between 33.3% ( 18 ) and 55.3% ( 19 ) in asymptomatic patients. Wagenhäuser et al described an overall sensitivity of 46.7% ( 20 ), meanwhile, Treggiari et al found the overall sensitivity at 66.8% ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant results were obtained between positive and negative rapid antigen test when compared with C q values of individual target genes obtained from RT-PCR. A study conducted by Tregiarri et al too demonstrated the statistically significant result ( p < 0.001) when Ag-RDT data were compared to that of C q values obtained [ 41 ].…”
Section: Discussionmentioning
confidence: 99%